The Regulation of Plasma Gelsolin by DNA Methylation in Ovarian Cancer Chemoresistance - Manzoor, Hafiza Bushra (Université d'Ottawa / University of Ottawa, 2023)
Ovarian cancer (OVCA) is the most lethal gynecologic cancer. Chemoresistance remains a major hurdle to successful therapy and patient survival. The secreted isoform of the actin-associated protein, gelsolin (plasma gelsolin; pGSN), is highly expressed in chemoresistant than chemosensitive OVCA cells, although the mechanism underlying the differential expression is not known. Also, its overexpression significantly correlates with shortened survival of OVCA patients. DNA methylation plays a key role in the regulation of genes expression and contributing to cancer development and chemoresistance with the help of DNA methyltransferases (DNMTs) or Ten eleven translocation (TETs) enzymes. TET1 is the most studied isoform of TETs family and primarily responsible for 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) oxidation to initiate demethylation and increase in the expression of methylated genes. Whether pGSN expression in OVCA cells is regulated by DNA methylation and TET1 regulates the differential pGSN expression between chemosensitive and resistant OVCA cells is not known. In this study, we hypothesized pGSN overexpression in chemoresistant OVCA cells is due to the hypomethylation at its promoter region by TET1. Our objective was to investigate whether DNA methylation and specifically TET1 plays a role in the regulation of differential pGSN expression and chemosensitivity in OVCA. Chemosensitive and resistant OVCA cell lines of different histological subtypes were used in this study to measure pGSN and TET1 mRNA abundance and protein contents by qPCR and Western blotting respectively. Cisplatin-induced chemoresponsiveness was morphologically assessed by Hoechst staining (apoptosis). Infinium HumanMethylation450 BeadChip assay was used for global methylation analysis of twelve (12) different OVCA cells and to investigate the role of DNA methylation specifically in pGSN regulation and pGSN-induced chemoresistance. DNMTs and TETs were pharmacologically inhibited in sensitive and resistant OVCA cell using specific inhibitors. Gain-and-loss-of-function assays were carried to identify the relationship between TET1 and pGSN in OVCA chemoresponsiveness. Differential protein and mRNA expressions of pGSN and TET1 were observed between sensitive and resistant OVCA cells and cisplatin reduced their expression in sensitive but not in resistant cells. Global methylation analysis revealed hypomethylation in resistant cells compared to sensitive cells. Pharmacological inhibition of DNMTs increased pGSN protein levels in sensitive OVCA cells and decreases their responsiveness to cisplatin, however we did not observe any difference in methylation level at pGSN promoter region. TETs inhibition resulted in hypermethylation at multiple CpG sites and decreased pGSN protein level in resistant OVCA cells which was also associated with enhanced response to cisplatin, findings that suggested the methylation role of TETs in the regulation of pGSN expression in OVCA cells. Further, we found that TET1 is inversely related to pGSN and positively related to chemoresponsiveness of OVCA cells. This project does not only broaden our knowledge about the mechanistic insights into the epigenetic regulation of pGSN in OVCA chemoresistance, but it also reveals a new potential target to re-sensitize chemotherapy resistant OVCA cells. This may provide a future strategy to improve overall OVCA patient survival.
Keywords: Ovarian Cancer; Chemoresistance; Epigenetics; DNA Methylation; Plasma Gelsolin; Ten Eleven Translocation Enzyme 1